THE CAUSE OF THE LACK OF WELFARE OF FOOD CROP FARMERS IN 2021 (JURNAL ECONOMICA : Research of Economic And Economic Education, 2021)
The agricultural sector makes a very positive contribution when Indonesia's economic growth experiences contraction (negative growth) in 2020. The contribution of the agricultural sub-sector will be dominant in the positive growth of the agricultural sector. However, in 2021 this sub-sector will have a different fate. The peak was in the second quarter of 2021, this growth sub-sector experienced a contraction of -8.16 percent, even though Indonesia's economic growth had only experienced positive growth. This is presumably due to the decline in the welfare of food crop farmers. It can be seen that throughout 2021 the exchange rate for food crop farmers (NTPP) has a value below 100. With a descriptive analysis by looking at the components that affect Indonesia's NTPP value. that there is a gap between the price index received (It) by farmers and the price consumed by farmers (Ib). this gap becomes negative because the value of It < Ib. The low is because farmers' income, especially paddy commodities, decreased compared to 2020. Meanwhile, the increase in Ib was due to an increase in household consumption (KRT) in the form of work, food and health as well as the consumption of Production Costs and Additional Capital Goods (BPPBM) on labour wages, capital goods and fertilizers & pesticide. It can be seen that there are many components that have to be solved and involve many parties.